1988
DOI: 10.1037/0022-0663.80.4.524
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory analogies can help children acquire information from expository text.

Abstract: This paper reports an experiment that investigated whether children can profit from the use of explanatory analogies to acquire information from expository text. Five-year old (N=24) and 7-year old (N=34) children listened to four texts describing relatively unfamiliar topics with or without explanatory analogies. The children were asked to recall the information described in the texts and to communicate this information to another child. They were also asked a number of inferential questions about the topics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 48 publications
1
31
0
1
Order By: Relevance
“…It was noted that analogies map information from a source domain onto a target domain. Pilot data revealed that such explicit instructions greatly facilitate participants' understanding and use of analogical passages, a finding that is common in this literature (see Bisanz, Bisanz, & Lefevre, 1984;Donnelly & McDaniel, 1993;Gentner, 1989;Gick & Holyoak, 1980;Reed, Ernst, & Banerji, 1974;Vosniadou & Schommer, 1988).…”
Section: Methodsmentioning
confidence: 67%
“…It was noted that analogies map information from a source domain onto a target domain. Pilot data revealed that such explicit instructions greatly facilitate participants' understanding and use of analogical passages, a finding that is common in this literature (see Bisanz, Bisanz, & Lefevre, 1984;Donnelly & McDaniel, 1993;Gentner, 1989;Gick & Holyoak, 1980;Reed, Ernst, & Banerji, 1974;Vosniadou & Schommer, 1988).…”
Section: Methodsmentioning
confidence: 67%
“…Examples are descriptions of mechanical models, concrete advance organizers, and metaphors (Mayer & Bromage, 1980;Royer & Cable, 1976;Simons, 1984;Vosniadou & Schommer, 1988). These analogies are considered to help in bridging the gap between what is already known and what should be learned, by acting as a frame into which the new concepts could be integrated.…”
Section: Instructional Methods Aimed At Integrationmentioning
confidence: 99%
“…Traditionally, analogies are one type of imagery employed with success, (Vosniadou, & Schommer, 1988;Dupin, & Joshua, 1989;Halpern, Hansen, & Riefer, 1990;Duit, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Studies aimed at improving scientific text design have considered: (a) coherence textual changes, (e.g., Kintsch, & Yarbrough, 1982;McNamara, Kintsch, Songer, & Kintsch, 1996); linking textual changes, (e.g., Vosniadou, & Schommer, 1988;Dupin, & Joshua, 1989); and, (c) the two kinds of textual changes simultaneously, (e.g., Beck et al, 1991; Britton, & Gü lgöz, 1991). However an exhaustive literature search does not reveal any study on the combination of the two kinds of textual changes separately and in tandem to test the effect of each possible element and of their combination on different levels of comprehension.…”
Section: Introductionmentioning
confidence: 99%